REFLECTIONS OF HALABJAH EARTHQUAKE EFFECTS ON THE STRUCTURAL BUILDING DAMAGES IN HALABJAH AND DARBANDIKHAN - ABDULLAH, WRYA; RAFIQ, SERWAN KHORSHEED; ALSHKANE, YOUNIS M. (Journal of Duhok University, 2021)
Earthquakes hit the earth on daily basis with different intensities. An earthquake of M 7.3 hit Halabjah on 12th of November 2017 and caused structural damages in both Halabjah and Darbandikhan. This paper investigates the reflections of seismic effects on the most structural damages found in the areaspresenting a thorough site investigation on the possible reasons behind the building failures and collapses and specifying the probable errors in their constructions and designs. Additionally, some of the most novel techniques of retrofitting are proposed to rehabilitate the damages in the buildings. After the investigation, it is deduced that, most of the structural failures can be attributed to lack of knowledge about lateral loads and not considering them in the design and construction of the buildings in those vicinities. Further, the construction level of the buildings can be considered as unsatisfactory in the affected areas for some serious problems mentioned in detail in the paper. Therefore, most of the buildings needed immediate rehabilitation and some of the most modern methods are proposed in doing so. As a result, it is proved that a proper balance has to be guaranteed between strength, stiffness and ductility in designing buildings to withstand lateral forces from an earthquake.